Hydrogen corporatism and working time reduction: Union strategies in the transformation of German primary steel manufacturing - Stefan Schoppengerd (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
Industrial trade unions in Europe and North America often struggle to develop a coherent strategy on climate change and overcoming fossil fuel production patterns. Trade union policy in the German steel industry is an interesting example of this: the "green" restructuring is firmly in favour, as it is easily compatible with positions on maintaining production sites. However, the hydrogen technology required for this brings with it new contradictions. At the same time, the IG Metall trade union recently held a collective bargaining round on reducing working hours in the socio-ecological transformation. This working paper analyses this situation by reconstructing the fundamental structures of industrial relations, the coming hydrogen economy and working time policy.
Keywords: J51; J59; L50; L61; O14; Q55; 330; Steel; Hydrogen; Working Time Policy; Just Transition; Socio-Ecological Transformation